1999
DOI: 10.1177/104649649903000601
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intergroup Competition and Assigned Group Goals on Group Efficacy and Group Effectiveness

Abstract: Goal setting and competition are two motivation techniques that are thought to have similar effects on goal variables and performance. This study tests the proposition that assigned goals and competition are similar in their effect. The effects of intergroup competition and assigned group goals on a group's efficacy, goals, productivity, and inefficiency were tested, using 351 undergraduate business students in 117 production work groups, in a 2 x 2 design. Intergroup competition increased the groups'efficacy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 51 publications
5
32
0
3
Order By: Relevance
“…Studies of group goal-setting have consistently shown a positive relationship between goal difficulty and task performance, thus replicating one of the commonly observed goal effects at the individual level (e.g., Mitchell, & Silver, 1990;Mulvey & Ribbens, 1999).…”
Section: Implicit Theories Of Ability In Groupssupporting
confidence: 53%
“…Studies of group goal-setting have consistently shown a positive relationship between goal difficulty and task performance, thus replicating one of the commonly observed goal effects at the individual level (e.g., Mitchell, & Silver, 1990;Mulvey & Ribbens, 1999).…”
Section: Implicit Theories Of Ability In Groupssupporting
confidence: 53%
“…All of these factors can potentially increase the level of group ef®cacy in the group. With regard to group effectiveness, studies have generally demonstrated a positive impact of group goal-setting (Gowen, 1986;Matsui et al, 1987;Mesch et al, 1994;Mitchell and Silver, 1990;O'Leary-Kelly et al, 1994;Mulvey and Ribbens, 1999). For example, in a meta-analysis of ten group goal-setting studies, O' Leary-Kelly et al (1994) found that the effect size for group goals on group performance was large (d 0.92).…”
Section: Goal-setting Trainingmentioning
confidence: 96%
“…Stanne dkk. (1999) hasil meta-analisis menunjukkan bahwa persaingan antarkelompok dapat meningkatkan kinerja dalam lingkungan kerja (Erev, Bornstein, & Galili, 1993), kelompok produktivitas (Mulvey & Ribbens, 1999), dan kinerja akademik (Okebukola, 1985(Okebukola, , 1986 Sansone dan Harackiewicz, (1996) membedakan dua cara kompetisi yang dapat memengaruhi motivasi intrinsik. Pertama adalah konteks kompetitif dijelaskan pada awal suatu kegiatan, yang dapat memengaruhi bagaimana individu menyelasiakan tugas.…”
Section: Diskusiunclassified